Calcium in Vascular Smooth Muscle Cell Elasticity and Adhesion: Novel Insights Into the Mechanism of Action - Zhu, Yi; Qu, Jing; He, Li; Zhang, Feng; Zhou, Zijing; Yang, Shanzhong; Zhou, Yong (Frontiers in Physiology, 2019)
Vascular smooth muscle cells (VSMCs) are the predominant cell type in the arterial wall. These cells play a critical role in maintaining vascular homeostasis including vasoconstriction and vasodilatation through active contraction and relaxation. Dysregulation of VSMC function alters the response of blood vessels to mechanical stress, contributing to the pathogenesis of vascular diseases, particularly atherosclerosis and hypertension. The stiffness of VSMCs is a major regulator of vascular function. Previous studies suggest that intracellular Ca2+ controls the stiffness of VSMCs by a mechanism involving myosin contractile apparatus. More recent studies highlight important functions of cytoskeletal α-smooth muscle actin (α-SMA), α5β1 integrin, and integrin-mediated cell-extracellular matrix (ECM) interactions in Ca2+-dependent regulation of VSMC stiffness and adhesion to the ECM, providing novel insights into the mechanism of calcium action.